Analisis Model Kecepatan Gelombang-P pada Coal-Seam Gas Studi Kasus Cekungan Sumatera Selatan, Indonesia - Harnanti Yogaputri Hutami; Fitriyani Fitriyani; Tiara Larasati Priniarti; Handoyo Handoyo (Engineering Faculty Universitas Lampung, 2020)
The rock physics model is one effective yet challenging way to investigate the coal-seam gas potential in Indonesia. However, because of the complex conditions of the Coal-Seam Gas Reservoirs, it is difficult to establish models. Despite the scarce modeling, this study aims to estimate the relation of gas-saturated within pores of coal seam to the elastic properties of rock, which is P-wave velocity. First, the coal seam minerals are applied to quantify matrix moduli using the Voigt-Reuss-Hill Average method. Pride’s simple equation is used to estimate the elastic properties of the coal seam at dry condition (zero gas saturation). Finally, Biot-Gassmann’s theory is applied to determine the elastic properties of coal seam with fully gas saturated. As the result, the proposed model showed that there is a significant negative correlation between gas content with both density and P-wave velocity of the coal seam. Finally, this P-wave velocity model of gas-saturated coal seams should be properly useful as the quick look for identifying coal seam gas potentials.